Surface phase defects induced downstream laser intensity modulation in high-power laser facility. (2nd March 2016) - Zhang, Xin; Zhou, Wei; Dai, Wanjun; Hu, Dongxia; Deng, Xuewei; Huang, Wanqing; Zhou, Lidan; Yuan, Qiang; Huang, Xiaoxia; Wang, De'en; Yang, Ying
Abstract : Optics surface phase defects induced intensity modulation in high-power laser facility for inertial confinement fusion research is studied. Calculations and experiments reveal an exact mapping of the modulation patterns and the optics damage spot distributions from the surface phase defects. Origins are discussed during the processes of optics manufacturing and diagnostics, revealing potential improvements for future optics manufacturing techniques and diagnostic index, which is meaningful for fusion level laser facility construction and its operation safety.